2019
DOI: 10.1089/cmb.2019.0114
|View full text |Cite
|
Sign up to set email alerts
|

Gene Regulatory Networks Governing the Generation and Regeneration of Blood

Abstract: Blood is an example of a highly regenerative tissue and its regeneration depends on the presence of stem cells residing in the bone marrow in humans. A better understanding of how these stem cells are programmed would benefit their use in clinical practice and shed light on the mechanisms by which the unique properties of stem cells are established. Our approach is to delineate the gene regulatory networks (GRNs) that specify these cells during their development in the embryo, and we use the amphibian experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This transition involves changes from an endothelial transcriptional program to a program promoting HC identity, morphology, and function (Swiers et al, 2013). Although the precise program directing the generation of HSCs during EHT is as yet unknown, important molecular and physiological aspects of HSC generation are conserved between zebrafish, chick, Xenopus, mouse, and human (Ciau-Uitz and Patient, 2019;Dzierzak and Bigas, 2018;Ivanovs et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This transition involves changes from an endothelial transcriptional program to a program promoting HC identity, morphology, and function (Swiers et al, 2013). Although the precise program directing the generation of HSCs during EHT is as yet unknown, important molecular and physiological aspects of HSC generation are conserved between zebrafish, chick, Xenopus, mouse, and human (Ciau-Uitz and Patient, 2019;Dzierzak and Bigas, 2018;Ivanovs et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In vertebrate embryos, HSCs arise in the aorta-gonad mesonephros (AGM) region from hemogenic endothelial cells (HECs). HECs undergo a highly-conserved 'endothelial-tohematopoietic transition' (EHT) process (Ciau-Uitz & Patient, 2019, Dzierzak & Bigas, 2018, Dzierzak & Speck, 2008, Jaffredo, Nottingham et al, 2005. Transcriptomics and loss-of-function studies have identified candidate regulators/signaling pathways in transitioning cells (Gao, Chen et al, 2020, Li, Gao et al, 2017, Lichtinger, Ingram et al, 2012, Moignard, Woodhouse et al, 2015, Porcheri, Golan et al, 2020, Swiers, Baumann et al, 2013, Zhou, Li et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…In the AGM region, definitive HSPCs are generated through a trans-differentiation process from a specialized endothelial cell (EC) compartment with hematopoietic potential (hemogenic endothelial cells or HECs). This process of endothelial-to-hematopoietic transition (EHT) is conserved between mammalian and non-mammalian vertebrates (Ciau-Uitz and Patient, 2019; Ivanovs et al, 2017; Bertrand et al, 2010; Boisset et al, 2010; Kissa and Herbomel, 2010; Zovein et al, 2008; de Bruijn et al, 2002; North et al, 2002; Medvinsky and Dzierzak, 1996; Muller et al, 1994; Dieterlen-Lievre, 1975) . In mice, EHT events occur between embryonic days (E)10.5-E12.5.…”
Section: Introductionmentioning
confidence: 99%